Lime pretreatment of sugar beet pulp and evaluation of synergy between ArfA, ManA and XynA from Clostridium cellulovorans on the pretreated substrate - Dredge, Roselyn (Springer Berlin Heidelberg, 2011)
Sugar beet pulp (SBP) is a waste product from the sugar beet industry and could be used as a potential biomass feedstock for second generation biofuel technology. Pretreatment of SBP with ‘slake lime’ (calcium hydroxide) was investigated using a 2(3) factorial design and the factors examined included lime loading, temperature and time. The pretreatment was evaluated for its ability to enhance enzymatic degradation using a combination of three hemicellulases, namely ArfA (an arabinofuranosidase), ManA (an endo-mannanase) and XynA (an endo-xylanase) from C. cellulovorans to determine the conditions under which optimal activity was facilitated. Optimal pretreatment conditions were found to be 0.4 g lime/g SBP, with 36 h digestion at 40 °C. The synergistic interactions between ArfA, ManA and XynA from C. cellulovorans were subsequently investigated on the pretreated SBP. The highest degree of synergy was observed at a protein ratio of 75% ArfA to 25% ManA, with a specific activity of 2.9 U/g protein. However, the highest activity was observed at 4.2 U/g protein at 100% ArfA. This study demonstrated that lime treatment enhanced enzymatic hydrolysis of SBP. The ArfA was the most effective hemicellulase for release of sugars from pretreated SBP, but the synergy with the ManA indicated that low levels of mannan in SBP were probably masking the access of the ArfA to its substrate. XynA displayed no synergy with the other two hemicellulases, indicating that the xylan in the SBP was not hampering the access of ArfA or ManA to their substrates and was not closely associated with the mannan and arabinan in the SBP.